Sosialisasi Dan Pemeriksaan Kadar Glukosa, Asam Urat Dan Kolesterol Dalam Pelaksanaan Identifikasi Kesehatan Masyarakat - Nasution, Nurhafizah; Riskawaty, Heny Marlina; Nursiah, Andi; Marpaung, Mauritz Pandapotan; Alfiraza, Ery Nourika; Hanif, Muhammad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Blood glucose is a sugar found in the blood formed from carbohydrates in food and stored as glycogen in the liver and skeletal muscles. Insulin and glucagon, two hormones derived from the pancreas, can affect blood glucose levels. Insulin is needed for the permeability of cell membranes to glucose and for the transport of glucose into cells. The purpose of the Community Service program is to conduct random blood sugar, uric acid and cholesterol level checks. The methods used in Community Service activities are socialization and health education and examination of glucose, uric acid and cholesterol levels in the implementation of community health identification. The results of the implementation of the uric acid, blood sugar and cholesterol level checks carried out in the community went well and understood the importance of regular and regular blood pressure and uric acid checks. The conclusion is that the Community Service program was successful and successfully implemented and was able to increase public understanding of the importance of early detection. The community response that was carried out in participating in the activities was quite good. Public knowledge about Glucose, Uric Acid and Cholesterol Levels and their prevention showed a remarkable increase.